Rethinking Fiduciary Security Execution in Debtor Default Disputes: Case Study of Decision No. 297/Pdt.G/2023/PN BPP - Ananto, Riana Wulandari (Reformasi Hukum, 2025)
Fiduciary security agreements grant creditors the right to execute secured assets without prior judicial authorization, provided that the security has been duly registered and evidenced by a Fiduciary Security Certificate under Law No. 42 of 1999. However, the execution of fiduciary collateral in debtor default disputes continues to raise questions regarding the limits of creditor authority and the protection of debtor rights. This study examines the legal basis and procedural mechanism of fiduciary security execution in cases of default, with particular attention to the principles of legal certainty, utility, and justice. Employing a normative legal method, the research analyzes statutory provisions, doctrinal interpretations, and judicial reasoning, focusing on Decision No. 297/PDT.G/2023/PN Bpp. The findings indicate that courts recognize the enforceability of fiduciary execution without litigation when formal registration requirements are satisfied, while rejecting additional claims such as material damages and coercive penalties due to insufficient legal grounds. The study concludes that fiduciary execution remains legally valid within the existing statutory framework but must be conducted proportionally and in a manner that respects debtor protections. Clear procedural standards and consistent oversight are therefore necessary to ensure a balanced and predictable secured transactions regime.